The Correlation between the Degree of Enophthalmos and the Extent of Fracture in Medial Orbital Wall Fracture Left Untreated for Over Six Months: A Retrospective Analysis of 81 Cases at a Single Institution - Yun Sik Sung; Chan Min Chung; In Pyo Hong (Archives of Plastic Surgery, 2013)
Background In patients with medial orbital wall fracture, predicting the correlation between the degree of enophthalmos and the extent of fracture is essential for deciding on surgical treatment. We conducted this retrospective study to identify the correlation between the two parameters. Methods We quantitatively analyzed the correlation between the area of the bone defect and the degree of enophthalmos on computed tomography scans in 81 patients with medial orbital wall fracture who had been left untreated for more than six months. Results There was a significant linear positive correlation between the area of the medial orbital wall fracture and the degree of enophthalmos with a formula of E=0.705A+0.061 (E, the degree of enophthalmos; A, the area of bone defect) (Pearson's correlation coefficient, 0.812) (P<0.05). In addition, that there were no cases in which the degree of enophthalmos was greater than 2 mm when the area of the medial orbital wall fracture was smaller than 1.90 cm2. Conclusions Our results indicate not only that 2 mm of enophthalmos corresponds to a bone defect area of approximately 2.75 cm2 in patients with medial orbital wall fracture but also that the degree of enophthalmos could be quantitatively predicted based on the area of the bone defect even more than six months after trauma.